Experimental and theoretical studies on the enhanced photoluminescence activity of zinc sulfide with a capping agent - de Santana, Yuri V. B.; Raubach, Cristiane W.; Ferrer, Mateus M.; La Porta, Felipe [UNESP]; Sambrano, Julio R. [UNESP]; Longo, Valeria M. [UNESP]; Leite, Edson R. [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2011)
The photoluminescence (PL) emission from zinc sulfide (ZnS) synthesized by the microwave-assisted solvothermal method in the presence/absence of a capping agent was examined to understand the key role of its PL activity. In addition, we also investigated the electronic structure using a first-principle calculation based on density functional theory (DFT) applied to periodic models at B.LYP level. Two models were selected to simulate the effects of structural deformation on the electronic structure; the ordered o-ZnS model and the disordered d-ZnS model, dislocating the Zn atom, 0.1 angstrom, in the z-direction. The PLemission in the visible region showed different peak positions and intensities in capped and uncapped ZnS. The PL emission was linked to distinct distortions in lattices and the emission of two colors, green in the capped and blue in the uncapped, was also examined in the light of favorable structural and electronic conditions. The computational simulations indicate that the electronic behavior can be associated with the new electronic levels above the valence band. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3666070]